Investigating Civilian Casualties in Time of Armed Conflict and Belligerent Occupation: Manoeuvring Between Legal Regimes and Paradigms for the Use of Force - Margalit, Alon (International Humanitarian Law Series, 2018)
In Investigating Civilian Casualties Alon Margalit discusses the appropriate response to State-caused fatalities. Highlighting various legal and practical challenges, the State's duty to investigate is considered amid increasing public scrutiny and influence of human rights law during military operations.